Epitaxial garnet films for microwave electronics - Yushchuk, Stepan; Yuryev, Sergij (Видавництво Національного університету «Львівська політехніка», 2002)
The technology of growth the substituted yttrium-iron monocrystalline garnet films (YIG) on the monocrystalline substrates of the gallium-gadolinium garnet (GGG) with the orientation (111) by the isotermal dipping method of liquid phase epitaxy was carried out. The penetration of La3+ ions into structure of YIG leads to decreasing of lattice mithmatch between the ferrite film and substrate .The control of growth speed of the epitaxial films on the whole process of growing and application of the compulsory mixing of melt-solution of oxides enables to receive the films with homogeneous thickness and small magnetic losses. The penetration into the YIG structure films the non-magnetic Ga3+ and La3+ ions considerably improves their thermostabillity without an essential increasing of the ferromagnetic resonance linewidth (FMR).
Keywords: yttrium-iron garnet; epitaxial film; ferromagnetic resonance; magnetization; substitution